The Effectiveness of Graphic Organizers as a Strategy in Comprehending Narrative Reading Texts for Senior High School Students - Erica Mardianti (Universitas Negeri Surabaya, 2026)
This study aims to determine the effect of using graphic organizers as a strategy on students' ability to understand narrative text. The study employed a quasi-experimental design with a pretest-posttest control group format. The sample consisted of two 10th-grade classes from a high school in Gresik, selected through convenience sampling. Data analysis was conducted using a t-test, and the effect size was calculated using the eta squared (η²) formula. The findings showed that the use of graphic organizers had a significant impact on students’ comprehension of narrative texts (p = 0.02 < 0.05). Based on the results of manual calculation, the η² value of 0.1305 was obtained, which, referring to Cohen (2007) criteria, is included in the small effect category. Although it falls into the small effect category, the positive change is still visible, which indicates that graphic organizers can be an alternative learning method that supports the reading comprehension process. The experimental group showed that they had an advantage in reading comprehension, which can be seen from their ability to identify and explain the main idea in their own words, effectively find supporting information through group discussions and practice questions, and make logical inferences by connecting information in the text with prior knowledge. The findings suggest that English teachers can consider using graphic organizers-based strategies as an effective learning method, especially for understanding plot, character, and conflict in texts. Schools can support this strategy approach by providing teacher training and the necessary resources. From a theoretical point of view, this approach is proven to improve students' literacy skills and has potential as a basis for future research across different contexts and text types.